Penerapan Model Pembelajaran Ekspositori Untuk Meningkatkan Motivasi, Keaktifan, Kemampuan Memecahkan Masalah, Kolaborasi, Dan Hasil Belajar Siswa Dengan Pendekatan Saintifik Berbasis Lesson Study - Irmayanti, Elis; Surindra, Bayu; Prastyaningtyas, Efa Wahyu; Ayatik, Tri (Efektor, 2019)
Learning can be said to be effective if there is continuity between all its components, including the selection of methods, media, and appropriate learning strategies. In addition, the preparation of learning tools must also be considered in order to facilitate the learning process in the classroom, especially if the learning devices that have been prepared have gone through the process of identifying problems in the classroom and paying attention to student characteristics. The purpose of this research is to increase motivation, activeness, problem-solving skills, collaboration, and student learning outcomes through the application of expository learning models with a scientific approach based on lesson study. The method used in this research is based on a lesson study which consists of three-stage, namely: plan, do and see. From the result of research that has been done, it can be seen that the application of expository learning models with a scientific approach based on lesson study can have a positive impact on increasing motivation, activeness, problem-solving skills, collaboration, and being able to improve student learning outcomes.